Beyond refueling: Investigating the diversity of functions of migratory stopover events. Issue 1 (10th February 2021) - Linscott, Jennifer A; Senner, Nathan R
Abstract: Stopovers comprise a significant proportion of the time that many birds spend migrating, and researchers have long relied on these events to define and classify broader migratory strategies. Analyses of stopovers often assume that individuals stop primarily or exclusively in order to replenish energy stores, but other non-fueling behaviors have also been described during stopover events and can influence stopover incidence and duration. Here, we discuss the growing demand for understanding these non-fueling behaviors and for restoring the inherent behavioral complexity to stopover events. We begin by describing how light-weight tracking technologies allow researchers to follow individuals along their entire migratory journeys, capturing stopovers that controvert the traditional stop–refuel–resume paradigm. We then discuss 5 well-identified non-fueling behaviors—recovering, sleeping, waiting, information gathering, and social interactions—and examine how including these behaviors can alter interpretations of individual movement paths. Finally, we outline emerging directions for identifying these behaviors and look to larger implications for population management and site conservation along migratory flyways. Lay Summary: Many birds make stops during their migratory journeys, and they may have various reasons for stopping. In the past, researchers have investigated the role of energy stores in stopping decisions, but birds may also need to stop or prolong their time at a stopping site in order to recover from bodily stress, catch up on lost sleep, wait for travel conditions to improve, or reconvene with other migrants. Non-fueling behaviors have been more difficult to study, but novel approaches that combine individual movement data with information about ecological and physiological conditions along the way are offering insights into when and where they occur. Investigating non-fueling stopping behaviors can reveal a more complex story about how birds navigate the challenges of seasonal migration. Graphical Abstract: